MRI Features of Stroke-Like Episodes in Mitochondrial Encephalomyopathy With Lactic Acidosis and Stroke-Like Episodes - Cheng, Weiqin; Zhang, Yuting; He, Ling (Frontiers in Neurology, 2022)
Mitochondrial myopathy encephalopathy lactic acidosis and stroke like episodes (MELAS) is an important cause of stroke-mimicking diseases that predominantly affect patients before 40 years of age. MELAS results from gene mutations in either mitochondrial DNA (mtDNA) or nuclear DNA (nDNA) responsible for the wide spectrum of clinical symptoms and imaging findings. Neurological manifestations can present with stroke like episodes (the cardinal features of MELAS), epilepsy, cognitive and mental disorders, or recurrent headaches. Magnetic resonance imaging (MRI) is an important tool for detecting stroke-like lesions, accurate recognition of imaging findings is important in guiding clinical decision making in MELAS patients. With the development of neuroimaging technologies, MRI plays an increasingly important role in course monitoring and efficacy assessment of the disease. In this article, we provide an overview of the neuroimaging features and the application of novel MRI techniques in MELAS syndrome.